ESTABELECIMENTO DO TESTE DO COMETA EM HEMÓCITOS DE BIOMPHALARIA GLABRATA (SAY,1818) - Grazeffe, Vanessa Siqueira; Kawano, Toshie; Tallarico, LF; Murasaki, NH; Suzuki, MF; Okazaki, k; Kawano, T; Pereira, CAB; Nakano, E (Revista do Instituto Adolfo Lutz, 2006)
Ver PDF.